Competitive Intelligence Systems in Practice: Investigating Main Issues and Challenges Regarding Acceptance and Usage Behavior - Guechtouli Manelle (European Scientific Journal, ESJ, 2018)
Gathering information about competitors and understanding their position is a key issue for any organization. The objective of this paper is to identify the main internal issues when it comes to dealing with Competitive Intelligence Systems (CIS) acceptance and usage behavior. We apply the exploratory research method of grounded theory to analyze a CI System of a large industrial company. At a practical level, our study aims at helping managers understanding the important features related to CIS in the postimplementation stage. At a theoretical level, the aim is to address a gap by explain the several relationships between the different categories of contributing actors and identifying the major problems they face after implementing a CIS. Our study identifies 3 main emergent issues in terms of:1. Internal visibility of the system, 2. Legitimacy and recognition by the management 3. System’s technology adoption and use. Results are discussed and managerial implications are addressed.